Mdm2 Gene as Transcriptional Protein Antagonist of P53 in OSCC with Mir-218 Expression - Hanif, Hilmy Irsyadi; Zafar, Anis Fatimah; Puteri, Astari; Wati, Sisca Meida; Rahayu, Retno Pudji (Bhakta Dental Journal, 2024)
Background: Murine double minute-2 (Mdm-2) gene expressed overly to the various type of human cancers. Murine double minute-2 associates with p53 affecting negatively with its gene products for activation of its transcriptional function. These genes mainly expressed in oral squamous cell carcinomas with p53 mutation condition. MicroRNAs nowadays becoming a promising diagnostic and prognostic biomarkers for malignancy through the expression and regulating the transcriptional function. It is reported that mir-218 expression may indicate the occurrence of OSCC. Purpose: The literature describes the putative pathway and function of mdm2 gene as transcriptional antagonist function of p53 in OSCC of mir-218 expression. Review(s): The relationship of mdm2 with mir-218 expression in OSCC may indicate the alternative mechanism of p53 dysfunction condition. Downregulated mir-218 will tend less binding to promoter of p53 causing the mutant state. The overexpression of mdm-2 may constitute inactivation of p53. Conclusion: The study findings may suggest mdm2 protein causing in OSCC due alternative mechanism of p53 as downregulated expression of mir-218.